Improving the thermal stability, electroactive β phase crystallization and dielectric constant of NiO nanoparticle/C–NiO nanocomposite embedded flexible poly(vinylidene fluoride) thin films. Issue 31 (10th March 2016) - Thakur, Pradip; Kool, Arpan; Hoque, Nur Amin; Bagchi, Biswajoy; Roy, Swagata; Sepay, Nayim; Das, Sukhen; Nandy, Papiya
Abstract : Increasing β phase nucleation and formation of microcapacitors in flexible high dielectric NiO NPs/C–NiO NCs modified PVDF films. Abstract : Using a simple chemical precipitation process followed by sintering at 400 °C, NiO nanoparticles (NPs) and C–NiO nanocomposites (NCs) have been synthesized and characterized by X-ray diffraction, UV-visible spectroscopy, zeta potential measurement, field emission scanning electron microscopy and energy dispersive X-ray spectroscopy. Then, NiO NP or C–NiO NC loaded PVDF thin films were fabricated via a simple solvent casting or solution casting method. Thermogravimetric analysis confirmed good thermal stability of the nanocomposite films. Strong ion–dipole interaction between the negative surfaces of NiO NPs or C–NiO NCs and –CH2 dipoles of polymer chains leads to the formation of a long stabilized TTTT conformation, i.e. formation of large number of electroactive β polymorphs in the modified PVDF thin films. Detailed study of the dependency of the dielectric properties on filler content (NiO NPs/C–NiO NCs) and frequency illustrates significant increase in the dielectric constant in the three phase C–NiO NCs–PVDF system than in the two phase NiO NPs–PVDF system. The dielectric constant is found to be as large as 317.4 at 20 Hz with a relatively low tangent loss value, and good flexibility when 20 mass% C–NiO NCs is incorporated in the PVDF matrix. These results have been explained in terms of Maxwell–Wagner–Sillars interfacial polarization at the NiO NPs/C–NiO NCs and insulating polymer matrix interface, evolution of a conductive network and formation of a microcapacitive structure in the NiO NPs or C–NiO NCs modified PVDF thin films.